Gibberellin antagonizes jasmonate-induced defense against Meloidogyne graminicola in rice - Yimer, Henok Zemene; Nahar, Kamrun; Kyndt, Tina; Haeck, Ashley; Van Meulebroek, Lieven; Vanhaecke, Lynn; Demeestere, Kristof; Höfte, Monica; Gheysen, Godelieve (The New phytologist, 2018)
Gibberellin (GA) regulates various plant growth and developmental processes, but its role in pathogen attack, and especially nematode–plant interactions, still remains to be elucidated. An in-depth characterization of the role of GA in nematode infection was conducted using mutant lines of rice, chemical inhibitors, and phytohormone measurements. Our results showed that GA influences rice–Meloidogyne graminicola interactions in a concentration-dependent manner. Foliar spray of plants with a low concentration of gibberellic acid enhanced nematode infection. Biosynthetic and signaling mutants confirmed the importance of gibberellin for rice susceptibility to M. graminicola infection. Our study also demonstrates that GA signaling suppresses jasmonate (JA)-mediated defense against M. graminicola, and likewise the JA-induced defense against M. graminicola requires SLENDER RICE1 (SLR1)-mediated repression of the GA pathway. In contrast to observations from other plant–pathogen interactions, GA plays a dominant role over JA in determining susceptibility to M. graminicola in rice. This GA-induced nematode susceptibility was largely independent of auxin biosynthesis, but relied on auxin transport. In conclusion, we showed that GA–JA antagonistic crosstalk is at the forefront of the interaction between rice and M. graminicola, and SLR1 plays a central role in the JA-mediated defense response in rice against this nematode.